On the systematic position of some species of Chiloneus, Desbrochersella and Sciaphilus, with description of two new species and lectotype selection (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Perrin, Hélène (Zootaxa, 2016)
Chiloneus globulus sp. nov. and C. tenietensis sp. nov. from Algeria are described, illustrated and compared with closely related species. The following new combinations are proposed: Chiloneus barbaricus (González, 1970) from Desbrochersella, Chiloneus innotatus (Pic, 1927) from Sciaphilus, Desbrochersella diversepubens (Pic, 1904) and Desbrochersella microps (Desbrochers des Loges, 1897) from Chiloneus, Myochlamys convexiceps (Desbrochers des Loges, 1896), Polydrusus (Leucodrusus) henoni (Allard, 1869) and Sericopholus murinus (Desbrochers des Loges, 1896) from Chiloneus. The following new synonymies are proposed: Chiloneus alboscutellaris (Pic, 1917) as a junior synonym of Chiloneus submaculatus (Pic, 1917), Chiloneus curtipennis (Pic, 1917) as a junior synonym of Desbrochersella diversepubens (Pic, 1904), Chiloneus dividuus (Pic, 1904) as a junior synonym of Chiloneus pennatus (Faust, 1885), Chiloneus inhumeralis (Pic, 1903) as a junior synonym of Chiloneus chobauti (Desbrochers des Loges, 1897), Chiloneus nasutus (Desbrochers des Loges, 1897) as a junior synonym of Chiloneus pertusicollis (Fairmaire, 1868), Chiloneus nitens (Pic, 1904) as a junior synonym of Chiloneus cinerascens (Rosenhauer, 1856), Chiloneus insulanus (González, 1970) as a junior synonym of Chiloneus innotatus (Pic, 1927), Chiloneus pilosulus Normand, 1953 as a junior synonym of Chiloneus vaulogeri (Pic, 1896), Chiloneus ruficornis (Allard, 1869) as a junior synonym of Chiloneus pertusicollis (Fairmaire, 1868), Chiloneus seminitidus (Hustache, 1941) as a junior synonym of Chiloneus cinerascens (Rosenhauer, 1856), Chiloneus subannulipes (Pic, 1917) as a junior synonym of Chiloneus minutissimus (Pic, 1904), Chiloneus subglobatus (Desbrochers des Loges, 1892) as a junior synonym of Chiloneus chevrolati Tournier, 1874, Chiloneus theresae (Pic, 1945) as a junior synonym of Chiloneus brevithorax Desbrochers des Loges, 1874, Chiloneus tuniseus (Desbrochers des Loges, 1897) as a junior synonym of Chiloneus brevipilis Desbrochers des Loges, 1893, Desbrochersella nitidipennis Pic, 1927 as a junior synonym of Chiloneus minutissimus (Pic, 1904), Pleurodirus alluaudi (Pic, 1903) as a junior synonym of Chiloneus vaulogeri (Pic, 1896), Sericopholus triangulifer (Desbrochers des Loges, 1903) as a junior synonym of Sericopholus murinus (Desbrochers des Loges, 1896). Lectotypes of the following species are designated (current names added in brackets when different): Alophinus triangulifer Desbrochers des Loges, 1903 (currently Sericopholus murinus (Desbrochers des Loges, 1896)), Alophinus triangulifer v. subuniformis Pic, 1904 (currently Sericopholus murinus (Desbrochers des Loges, 1896)), Chiloneus algericus Desbrochers des Loges, 1871 (currently Chiloneus infuscatus (Chevrolat, 1861)), Chiloneus brevi-pilis Desbrochers des Loges, 1893, Chiloneus carinidorsum Desbrochers des Loges, 1871, Chiloneus chevrolati Tournier, 1874, Chiloneus murinus Desbrochers des Loges, 1896 (currently Sericopholus murinus (Desbrochers des Loges, 1896)), Chiloneus ottomanus Desbrochers des Loges, 1892, Chiloneus veneriatus Normand, 1937, Eusomus sphaeropterus Allard, 1869 (currently Chiloneus pertusicollis (Fairmaire, 1868)), Foucartia ruficornis Allard, 1869 (currently Chiloneus pertusicollis (Fairmaire, 1868)), Holcorhinus parvus Stierlin, 1899 (currently Chiloneus chevrolati Tournier, 1874), Platytarsus vaulogeri Desbrochers des Loges, 1897 (currently Chiloneus barbaricus (González, 1970)), Sciaphilus alboscutellaris Pic, 1917 (currently Chiloneus submaculatus (Pic, 1917)), Sciaphilus alluaudi Pic, 1903 (currently Chiloneus vaulogeri (Pic, 1896)), Sciaphilus chobauti Desbrochers des Loges, 1897 (currently Chiloneus chobauti (Desbrochers des Loges, 1897)), Sciaphilus convexiceps Desbrochers des Loges, 1896 (currently Myochlamys convexiceps (Desbrochers des Loges, 1896)), Sciaphilus curtipennis Pic, 1917 (currently Desbrochersella diversepubens (Pic, 1904)), Sciaphilus diversepubens Pic, 1904 (currently Desbrochersella diversepubens (Pic, 1904)), Sciaphilus dividuus Pic, 1904 (currently Chiloneus pennatus (Faust, 1885)), Sciaphilus inhumeralis Pic, 1903 (currently Chiloneus chobauti (Desbrochers des Loges, 1897)), Sciaphilus innotatus Pic, 1927 (currently Chiloneus innotatus (Pic, 1927)), Sciaphilus microps Desbrochers des Loges, 1897 (currently Desbrochersella microps (Desbrochers des Loges, 1897)), Sciaphilus minutissimus Pic, 1904 (currently Chiloneus minutissimus (Pic, 1904)), Sciaphilus nasutus Desbrochers des Loges, 1897 (currently Chiloneus pertusicollis (Fairmaire, 1868)), Sciaphilus nitens Pic, 1904 (currently Chiloneus cinerascens (Rosenhauer, 1856)), Sciaphilus pertusicollis Fairmaire, 1868 (currently Chiloneus pertusicollis (Fairmaire, 1868)), Sciaphilus pruinosus Desbrochers des Loges, 1896 (currently Chiloneus pennatus (Faust, 1885)), Sciaphilus subannulipes Pic, 1917 (currently Chiloneus minutissimus (Pic, 1904)), Sciaphilus submaculatus Pic, 1917 (currently Chiloneus submaculatus (Pic, 1917)), Sciaphilus vaulogeri Pic, 1896 (currently Chiloneus vaulogeri (Pic, 1896)).
Keywords: Algeria; Body Size; Female; Animal Structures; Animal Distribution; velikost orgánu; Animals; Organ Size; ženské pohlaví; mužské pohlaví; Male; rozšíření zvířat; velikost těla; Weevils; zvířata; anatomické struktury zvířat; Alžírsko; nosatcovití